EMPIRICAL INVESTIGATION OF ORGANIC GROWTH, EVIDENCE FROM INDONESIAN PUBLIC LISTED COMPANIES - Stephanus Remond Waworuntu; Carina Tjhatra (Bina Nusantara University, 2010)
The main objective of this research is to examine Indonesian public listed companies with earnings generated organically rather than through earnings management, income manipulation, financial engineering, or through mergers and acquisitions. 70 samples were taken from Kompas 100 Stock Index from the period of 2004 to 2007 excluding banks, financial institutions, REITs and insurance companies. The authors applied the model of Organic Growth Index (OGI), developed by Hess (2007). The OGI model designed to illuminate value-creating companies that have consistently outperformed industry competition through organic growth. The test begins by selecting the best Economic Value Added and high growth companies. The result of our study shows that there are 10 percent of Indonesian public listed companies identified as OGI winners. These companies passed the core earnings test, income manipulation test and cash realization test, and thus indicated that those Indonesian public companies have a low level of earnings manipulation and low engagement in non-core earnings such as hedging activities.